FAUNA, FEATURES AND DISTRIBUTION OF BIRCH APHID (HOMOPTERA, APHIDINEA) IN CENTRAL ASIA - M. Kh. Akhmedov; A. K. Khusanov (Российский паразитологический журнал, 2019)
Objective of research: A study on fauna and biology of birch aphids in Central Asia. Materials and methods. This paper is based on collections, observations and experiments conducted in 1972-2016 in various areas of Central Asia (Uzbekistan, Kyrgyzstan). Collection and control of birch aphids were performed by common methods; aphids were fixed in test tubes with 96% ethanol. 102 birch aphids were investigated; they were applied for production of 311 total permanent preparations using the method of pre-maceration. The results of morphological changes in aphids were estimated by the common mathematical methods of statistics. Results and discussion. It was found that the fauna of birch aphids in Central Asia consists of 12 species and 1 suborder belonging to 6 genera ( Symydobius Mordvilko, 1894; Euceraphis Walker, 1870; Betulaphis Glendenning, 1926; Callipterinella van der Goot, 1913; Calaphis Walsh 1862; Clethrobius Mordvilko. 1928 ) of the subfamily Myzocallidinae , family Drepanosiphidae. Forage plants of birch aphids ( Semydobius oblongus von Heyd., Betulaphis quadrituberculata Kalt., Callipterinella betularia Kalt., Callipterinella tuberculata von Heyd., Calaphis betuliсola Kalt., Calaphis flava Mord., Clethrobius сomes Walk.) are widespread from temperate zones of the Northern Hemisphere to South Kazakhstan. Issyk-Kul region is the southernmost point of the spread of Euceraphis punctipennis and Callipterinella minutissima Str. in Central Asia. Euceraphis pilosa and its subspecies E.pilosa arslanbobica, Betulaphis hissarica and Callipterinella ferganica are natives in the Mountains of Central Asia. As elements of aphid fauna of the Angara region, they were being formed in mountain areas through the development of autochthons as well as conversion of allochthons to native species Among the aphids identified, we have described Callipterinella ferganica Akhmedov et Khusanov 2009 and Euceraphis pilosa arslanbobica Akhmedov et Khusanov ssp.n.